Zolpidem dependence with frontal lobe syndrome: a case report - Majumder, Udayan; Das, Rajesh; Singh, Rajkumar Lenin (International Journal of Basic & Clinical Pharmacology, 2017)
Zolpidem is a non-benzodiazepine sedative hypnotic that binds to the benzodiazepine binding site on the gammaaminobutyric acid type A (GABA-A) receptors. It is the most commonly prescribed sleep medication which has been shown to be effective for treating insomnia on a short-term basis with fewer side effects than traditional benzodiazepines, which are feared for their abuse and dependence potential. Many studies have reported efficacy and safety of zolpidem in treatment of insomnia keeping in mind about its low abuse, and dependence capability. We present a case of zolpidem dependence in a 36-year-old male to emphasize that zolpidem also should be judiciously prescribed under supervision so that it does not develop tolerance, abuse and dependence.